Analisis Tingkat Konsumtif Mahasiswa Manajemen UNIMED Stambuk 2023 Terhadap Pemakaian Produk Skintific - Alfahmi, Fikri; Kristin, Okta Viani; Meiriza, Mica Siar; Lubis, Nabila Boru; Kinanti, Anggita; Umaira, Nabila; Ramadhani, Aulia (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze people's perceptions of Skintific skin care products on the level of consumption. The results showed that the majority of respondents in this study claimed to agree that Skintific skin care products are an important part of their daily lives and are willing to spend part of their budget to buy these products. This research includes a type of causal associative research using a qualitative descriptive approach and quantitative methods which in analyzing data using the distribution of questionnaires and questionnaires to the public. The use of skin care products is influenced by the needs of each skin type and skin problems faced by each person. Skintific products are very popular thanks to their efficacy and effective ingredients in overcoming skin problems. Public consumption of skin care products is influenced by several factors such as personal beauty needs, treatment of skin problems, and lifestyle trends. The results show that the use of Skintific skincare products can increase people's consumption of skincare products. This research provides great insight into how Skintific skincare products are accepted by the public and their impact on consumption habits towards skincare products. The implications of these findings can be used by skincare companies to improve their marketing and development.